Best person or best mix? How public sector managers understand the merit principle. Issue 3 (15th December 2021) - Foley, Meraiah; Cooper, Rae; Colley, Linda; Williamson, Sue
Abstract: As public sector organisations around the world enact strategies to progress gender equality, managers are forced to navigate the apparent conflict between making employment decisions on individual‐level 'merit' and considering the collective constraints and disadvantage that occur along gender lines. In this paper, we investigate how managers' understandings of merit contribute to this tension. Analysing data collected in focus groups with 273 mid‐level public sector managers in four Australian jurisdictions where efforts to promote gender equality were actively under way, we found that many managers adhered to a highly individualised understanding of merit which precluded them from considering gender or addressing gendered inequality in their employment decisions. Only a small proportion of managers who believed that creating a more representative bureaucracy was a legitimate public sector objective were able to justify considering a candidate's gender as a source of merit. We argue that public sector organisations seeking to promote gender equality should focus managers' attention on the benefits of achieving a more representative bureaucracy and give managers greater normative and regulatory certainty about how to assess and apply merit in that context. Abstract : As public sector organisations around the world enact strategies to progress gender equality, managers are forced to navigate the apparent conflict between making employment decisions on individual‐level merit and considering the collective constraints and disadvantage that occur along gender lines. This paper investigates how managers' understandings of merit contribute to this tension.